NECROTIZING PNEUMONIA DUE TO RHODOCOCCUS HOAGII IN A PATIENT WITH ADVANCED RETROVIRAL DISEASE - Gan, Yi Lung; Chang, Chee Yik; Yusoff, Yuhin Karina; Radhakrishnan, Anuradha P. (Journal of Ayub Medical College Abbottabad, 2022)
Rhodococcus hoagii is a well-known zoonotic disease, especially in foals. Its occurrence in humans is uncommon and usually occurs in immunocompromised patients. We present a case of Rhodococcus hoagii infection resulting in necrotizing pneumonia in a patient with advanced retroviral disease who had defaulted treatment. Effective treatment of Rhodococcus hoagii infection requires a combination of antibiotics. We also highlighted the importance of effective communication between clinicians and microbiologists so that prompt treatment can be initiated to improve patient outcomes.